2012
DOI: 10.1155/2012/901483
|View full text |Cite
|
Sign up to set email alerts
|

Human-Robot Interfaces in Exoskeletons for Gait Training after Stroke: State of the Art and Challenges

Abstract: Robotic rehabilitation of CVA (stroke) survivors is an emerging field. However, the development of effective gait rehabilitation robots used to treat stroke survivors is and remains a challenging task. This article discusses existing approaches and gives an overview of limitations with existing wearable robots. Challenges and potential solutions are being discussed in this article. Most difficulties lie in the implementation of physical and cognitive human robot interfaces. Many issues like actuation principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…(1) El estudio y desarrollo de mejores interfaces cognitivas con los robots de rehabilitación (Lagoda et al, 2012). Esto incluye la extracción de comandos para la operación de robots a partir de variables biomecánicas (Frizera et al, 2011), la extracción de comandos para la operación del robot a partir de variables bioeléctricas (Barrios et al, 2012;Xu et al, 2014), y la extracción de información no intencional del operario (por ejemplo, temblores, clonus, espasmos o perturbaciones en general) para un control más robusto (Raya et al, 2010;Lambrecht et al, 2014).…”
Section: Robótica De Rehabilitación Y Asistenciaunclassified
“…(1) El estudio y desarrollo de mejores interfaces cognitivas con los robots de rehabilitación (Lagoda et al, 2012). Esto incluye la extracción de comandos para la operación de robots a partir de variables biomecánicas (Frizera et al, 2011), la extracción de comandos para la operación del robot a partir de variables bioeléctricas (Barrios et al, 2012;Xu et al, 2014), y la extracción de información no intencional del operario (por ejemplo, temblores, clonus, espasmos o perturbaciones en general) para un control más robusto (Raya et al, 2010;Lambrecht et al, 2014).…”
Section: Robótica De Rehabilitación Y Asistenciaunclassified
“…This is not a natural phenomenon and does not encourage the effected muscles or motor cortex to be activated during training. Patients can become passive when unmotivated yet the gait therapy will still continue although patient neuroplasticity is low which means learning is slow or nonexistent [7]. A better approach which is proposed is to 'detect' the patients intent through reading EEG signals and then impose relative robot movements to the leg.…”
Section: B Eeg Based Bcimentioning
confidence: 99%
“…This has advantages of alleviating the need of groups of therapists and physiotherapist fatigue but there is limited evidence that this type of robot assisted physical therapy has any improved outcomes over human administered therapy [6]. Studies have shown effective treatment is only achieved when the patient actively contributes to motion [7], which is not always the case when robots are rigidly guiding limbs on predefined trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the design of the underlying kinematic structure, that allows the wearer to move through the surrounding environment without feeling hindered, is not dependent on the deficiencies or capabilities of a particular user and is thus advantageous for all users of exoskeletal devices. In order to achieve this, a crucial step is to ensure that the kinematic structure of the exoskeleton is compatible with the human joints it assists [32].…”
Section: Introductionmentioning
confidence: 99%